Effects of two typical quinolone antibiotics in the marine environment on Skeletonema costatum - Lin, Yuxin; Li, Tiejun; Zhang, Yurong (Frontiers in Marine Science, 2024)
This study delved into the effects of levofloxacin (LEV) and norfloxacin (NOR), on Skeletonema costatum through analyzing changes in the cell growth, chlorophyll a (Chla) content, maximal quantum yield of PSⅡ (Fv/Fm), protein content, the enzyme activities of superoxide dismutase (SOD), glutathione reductase (GR), and glutathione peroxidase (GSH-PX) in the enzyme system, and the membrane lipid peroxidation product malondialdehyde (MDA) content of the non-enzymatic system under LEV and NOR exposure. The findings revealed both LEV and NOR inhibited the cells growth of microalgae cells, except for 10 mg/L NOR, which promoted growth. The algal cells were more sensitive to LEV. The 96-h half-maximal inhibitory concentrations (96h-IC50) of LEV and NOR were 14.770 mg/L and 44.250 mg/L. A low concentration of NOR (10 mg/L) promoted the Chla content, while high concentrations of both antibiotics (LEV > 20 mg/L, NOR > 100 mg/L) decreased the Chla content and Fv/Fm value of the microalgae. Therefore, antibiotics may impact photosynthesis through affecting the photosynthetic system of algae. Additionally, at high antibiotic concentrations (LEV > 20 mg/L, NOR > 100 mg/L), the protein and MDA content were reduced, while the GR, SOD, and GSH activities increased, Consequently, elevated levels of LEV and NOR induced significant oxidative stress. This study provides a comprehensive analysis of the impact of LEV and NOR on the growth of marine microalgae alongside an exploration of the underlying physiological mechanisms involved.These insights provide a foundation for evaluating the potential ecological risks posed by antibiotics in marine ecosystems.